2004
DOI: 10.1238/physica.regular.069a000c1
|View full text |Cite
|
Sign up to set email alerts
|

Two-Photon Decay in Heavy Atoms and Ions

Abstract: We review the status of and comment on current developments in the field of two-photon decay in atomic physics research. Recent work has focused on twophoton decays in highly-charged ions and two-photon decay of inner-shell vacancies in heavy neutral atoms. We emphasize the importance of measuring the shape of the continuum emission in two-photon decay as a probe of relativistic effects in the strong central fields found in heavy atomic systems. New experimental approaches and their consequences will be discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 87 publications
0
45
0
Order By: Relevance
“…Theoretical work on two-photon transitions started at the dawn of quantum mechanics [4]. Since then, theoretical and experimental work has mainly focused on H-like and He-like systems ( [5], and references therein). Various aspects of two-photon transitions, such as resonance effects [6], negative continuum effects [7], relativistic and QED effects [8], and higher-order multipole effects [9] on two-photon transitions in H-like ions, in these isoelectronic sequences of ions have been addressed in very recent (mostly theoretical) studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical work on two-photon transitions started at the dawn of quantum mechanics [4]. Since then, theoretical and experimental work has mainly focused on H-like and He-like systems ( [5], and references therein). Various aspects of two-photon transitions, such as resonance effects [6], negative continuum effects [7], relativistic and QED effects [8], and higher-order multipole effects [9] on two-photon transitions in H-like ions, in these isoelectronic sequences of ions have been addressed in very recent (mostly theoretical) studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, an accurate measurement of the experimental decay rate would constitute an ultimate benchmark of relativistic many-body theoretical methods and computational schemes. So far no experimental observations of E1M1 transitions in He-like or Be-like systems exist [5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the two-photon decay is sensitive to the electronic structure of the ions as a whole since, within the framework of perturbation theory, all intermediate bound and continuum states have to be taken into account in order to obtain the transition probabilities. Several lifetime measurements have been performed in the past for the 1s2s 1 S 0 state, and especially for low-and medium-Z ions along the helium isoelectronic sequence [5]. In these case studies, the lifetime of the 1s2s 1 S 0 state was found to be in good agreement with a number of nonrelativistic and relativistic calculations.…”
Section: Introductionmentioning
confidence: 55%
“…One such rare process is two-photon emission (TPE), which is especially important in atomic physics, astrophysics, and nuclear physics [7][8][9][10][11][12]. As the most basic multiphoton emission process, it is therefore appropriate to use TPE to study the coherent amplification of rare processes.…”
Section: Introductionmentioning
confidence: 99%